Anthropology and safeguarding of living cultural heritage in Gabon : the role of museums. - (:unkn) unknown (My University, 2019)
In recent decades, museums have multiplied in most African societies; each cultural sector, each community, each city wants its own, for prestige or to develop economic and tourism activity. As a result, the design of the museum has evolved in its form, objectives, organization and management. This has given rise to financial challenges, from which concepts such as the cultural enterprise and its relationship with the market, the preservation of collections and their enhancement through exhibitions open to different audiences have emerged. As the museum becomes a driving force in cultural policies, both at the national and local levels, Gabon is lagging behind in this area, despite its potential. However, a museum without a collection does not exist: it must be a place of exhibition or interpretation. And a museum without a public would be a reserve or a center for the study of collections. It is through the consumption of images of history in time and space that individuals' subjective experiences of cultural policy are shaped. This individual subjectivity leads us to conceive the museum differently. Today, however, this revision seems problematic, especially for a Gabonese man. Indeed, instead of being part of a more or less homogeneous local identity that is circumscribed within the national identity, it maintains broader ethnic ties because of personal, economic, professional or financial relationships that sometimes transcend the nation's geographical and cultural borders. Thus, in Gabon, the management of cultural heritage must take into account not only the benefits of its enhancement but also local actors. The aim is to enable local populations to benefit from the benefits of the enhancement of their heritage. For, unframed development leads to mass tourism with its disadvantage, namely the erosion of heritage and cultural values, caused by either natural or human degradation. This is why it is necessary to introduce a new approach that require
Keywords: African Research